Paint Shop Pro 9 for photographers : - McMahon, Ken (Elsevier/Focal, 2005)
This complete and easy-to-follow introduction to Jasc's Paint Shop Pro 9 allows readers to take this popular graphics and photo-editor program to heights that they would not imagine. McMahon places this package firmly within the context of digital imaging and the Web for images and animations with clear, step-by-step tutorials, eye-catching visuals and numerous tips and tricks.